Structural Phenomenon of Cement-Based Composite Elements in Ultimate Limit State - I. Iskhakov; Y. Ribakov (Advances in Materials Science and Engineering)
Cement-based composite materials have minimum of two components, one of which has higher strength compared to the other. Such materials include concrete, reinforced concrete (RC), and ferrocement, applied in single- or two-layer RC elements. This paper discusses experimental and theoretical results, obtained by the authors in the recent three decades. The authors have payed attention to a structural phenomenon that many design features (parameters, properties, etc.) at ultimate limit state (ULS) of a structure are twice higher (or lower) than at initial loading state. This phenomenon is evident at material properties, structures (or their elements), and static and/or dynamic structural response. The phenomenon is based on two ideas that were developed by first author: quasi-isotropic state of a structure at ULS and minimax principle. This phenomenon is supported by experimental and theoretical results, obtained for various structures, like beams, frames, spatial structures, and structural joints under static or/and dynamic loadings. This study provides valuable indicators for experiments’ planning and estimation of structural state. The phenomenon provides additional equation(s) for calculating parameters that are usually obtained experimentally and can lead to developing design concepts and RC theory, in which the number of empirical design coefficients will be minimal.